Problema Degradasi Budaya Sopan Santun Siswa Sekolah Dasar - Zulia Ningsih; Ghea Maurella Safira; Amiratul Naafi; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to identify and analyze the factors that cause the degradation of polite culture in elementary school students, as well as its impact on individuals and the school environment. It is hoped that this research can provide a comprehensive picture of this problem. It is hoped that the results of this research can become the basis for developing an effective intervention program to improve the culture of politeness in elementary school students. The degradation of the culture of politeness in elementary school students is a serious problem and requires serious attention. This research aims to identify effective solutions to overcome these problems. This research will examine various programs and approaches that have been implemented to improve the culture of courtesy. Apart from that, this research will also formulate policy and program recommendations that can be implemented in schools. The methodology used in this research is a literature review, with descriptive qualitative analysis from various literature sources. The results of the research show that the lack of strengthening etiquette values at home, school and society is the main factor in changes in student behavior. This research also formulates policy and program recommendations that can be implemented to improve character education in elementary schools. Apart from that, it is hoped that this research can provide practical solutions to overcome the degradation of polite culture, create a generation that is more civilized and appreciates social values.